ASSOCIATION OF SMOKING AND SEVERITY OF COVID-19 INFECTION AMONG 5, 889 PATIENTS IN MALAYSIA: A MULTI-CENTER OBSERVATIONAL STUDY. (March 2022) - Ismail, Norliana; Hassan, Noraryana; Abd Hamid, Muhammad Hairul Nizam; Yusoff, Ummi Nadiah; Khamal, Noor Raihan; Omar, Mohd Azahadi; Wong, Xin Ci; Pathmanathan, Mohan Dass; Mohd Zin, Shahanizan; Muhammad Zin, Faizah; Nik Mohamed, Mohamad Haniki; Mohd Nor, Norashidah
Highlights: Smoking affects the immune system and health of smokers. Smoking increased the risk of getting severe COVID-19 infection. Smokers had a higher risk of getting COVID-19 complications. COVID-19 brings an opportunity to highlight the benefits of quitting smoking. ABSTRACT: Objective: This study aims to investigate the association between smoking and the severity of COVID-19 infection during the initial wave of this pandemic in Malaysia. Methods: This is a multi-center observational study using secondary hospital data collected retrospectively from February 1, 2020, until May 30, 2020. Clinical records of all real-time polymerase chain reaction (RT-PCR)-confirmed COVID-19 cases with smoking status, co-morbidities, clinical features, and disease management were retrieved. Severity was assessed by the presence of complications and outcomes of COVID-19 infection. Logistic regression was used to determine the association between COVID-19 disease severity and smoking status. Results: A total of 5, 889 COVID-19 cases were included in the analysis. Ever smokers had a higher risk of having COVID-19 complications, such as acute respiratory distress syndrome (odds ratio [OR] 1.69; 95% confidence interval [CI] 1.09-2.55), renal injury (OR 1.55; 95% CI 1.10-2.14), and acute liver injury (OR 1.33; 95% CI 1.01-1.74), compared with never smokers. However, in terms of disease outcomes, there were no differences between the two groups. Conclusion: Although no significant association was found in terms of disease outcomes, smoking is associated with a higher risk of having complications owing to COVID-19 infection.